Synchrony nutrient capture via intercropping system from plant residues in a rejuvenated oil palm plantation - Kusuma, Alan Purba (2024)
Oil palm (Elaeis guineensis Jacq.) is a highly efficient crop that produces more oil per hectare of land compared to the other major oil crops worldwide. However, It typically has a life cycle of only about 23 - 25 years, when there are rising costs of production and falling profit in consequence of the palms being too tall for harvesting followed by significant yield drops due to pests and diseases. By this stage, replanting is normally carried out due to economic and safety considerations. Once replanting is done, there will be a ‘big loss’ of valuable nutrients stored in the previous planting, especially nitrogen (N), phosphorus (P), and potassium (K). Lacking information on the potential nutritional values of organic matter at replanting as well as inattentiveness on managing organic matter pool at replanting will economically harm the smallholders with smaller plantations and will rise an environmental issue related to N and P contamination in water bodies via leaching and run-off and emission to atmosphere via gaseous. Therefore, this study was conducted and framed into three sequential experiments, i.e. (1) quantifying the biomass and total N, P, and K stocks of above ground oil palm components from old plantings using destructive measurement, (2) determining the decomposition rates and the N, P, and K release rates of three major oil palm components (trunk, rachis, and leaflets) using litter-bag method, and (3) finding the best intercropping option in terms of profitable yield production and highly conservation of N derived from decomposing oil palm residues. Based on Experiment-1, total above-ground dry-biomass from a 24-year-old oil palm plantation was estimated to be about 83 MT/ha, where each hectare of oil palm residues contains at least 576 kg of N, 69 kg of P and 1641 kg of K. Based on Experiment-2, the decomposition rate constants ‘k’ for the leaflets, rachis, and the trunk were 0.045 per week, 0.029 per week, and 0.032 per week, respectively. The potential loss of N from the first couple years after replanting was also calculated to be roughly 326 kg per hectare. Meanwhile, the potential loss of P and K were approximately 36 kg/ha and 1378 kg/ha, respectively. Finally, based on Experiment-3, a combination between zea mays and Mucuna bracteata is expected to give a better synchrony. This combination is designed to reduce N loss by speeding up the N uptake by the faster planting cycle of maizeduring the first six months after planting which is when Mucuna bracteata is still growing and not entirely covering the soil surface. After harvesting, the corn cobs are delivered to the mill or warehouse, while the stover, which is high in nitrogen, is used to mulch the young oil palms. Once the biomass has completely covered the soil surface, Mucuna bracteata will take over the N conservation.